조직중심의 지자체 기능연속성계획(COOP) 수립방안 및 실행력 확보에 관한 연구 - 최혜령; 이영재; 정종수; Choi, Hye Ryoung; Lee, Young Jai; Cheung, Chong Soo (한국재난정보학회논문집, 2022)
Purpose: As an administrative organization that directly affects the safety and livelihood of the people, local governments are important to ensure the continuity of key functions in the event of a disaster. The purpose of this study is to review effective methods for establishing and implementing a continuity of operations plan to protect and maintain the key functions of local governments. Method: In order to improve the inefficiency of the ISO22301-based continuity of operation plan, applying the organizational-oriented functional continuity method and set up the planning method, key functions, required resources, and basic education and training forms, and apply to local governments and review their feasibility. Result: The proposed organization-oriented continuity of operation plan preparation method reflects the characteristics of bureaucratic local governments and makes it easy to prepare and apply in practice. Conclusion: Compared to the private sector, in the public sector, where work is organization-oriented, it can be a more efficient way to fully reflect the organizational point of view in establishing a continuity of Opertaions plan. 연구목적: 지자체는 국민의 안전과 생활에 직접적으로 영향을 주는 행정조직으로서 재난 발생 시 핵심 기능의 연속성 확보가 중요하다. 본 논문은 재난으로부터 지자체 핵심기능을 보호·유지하기 위한 기능연속성계획의 수립 및 실행력 확보를 위한 효율적인 방법을 검토하는 것을 목적으로 한다. 연구방법: ISO22301기반 한 기능연속성계획의 비효율성을 개선하기 위하여, 조직중심의 기능연속성 방법을 적용하여 계획수립 방안과 핵심기능, 소요자원 그리고 교육훈련에 관련된 기본 서식을 제시하고, 지자체에 적용하여 타당성을 검토한다. 연구결과: 제안된 조직중심의 기능연속성계획 작성 방법은 관료적인 지자체의 특성을 반영하여 실국 단위로 작성함으로써 작성 및 실무적용이 용이하다. 결론:민간에 비하여 업무가 조직중심으로 되어 있는 공공분야에서는 기능연속성계획 수립에 조직적인 관점을 충분히 반영하는 것이 더 효율적인 방법이 될 수 있다.